Determinan Cash Holdings dan Excess Value - Wahyuni, Iis; ., Soeratno; ., Suyanto (Institut Bisnis dan Informatika Kesatuan, 2017)
This research aim to analyze the determinants of cash holdings and the excess value on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period.Model research analysis using Structural Equation Modeling (SEM). The independent variables are firm size, leverage, cash flow, net working capital and growth equity. And the dependent variable is the excess cash holdings and value. This study uses panel data from 320 observational data of companies that have been listed in the Indonesia Stock Exchange in the period 2011-2015. The results showed that 1) cash flow, net working capital have significant effect on cash holdings. 2) leverage, firm size, growth equity doesn’t have significant effect on cash holdings. 3) cash holdings have significant effect on the excess value. 4) cash flow, net working capital, leverage doesn’t have significant effect on the excess value. 5) firm size, growth equity doesn’t have significant effect on the excess value.This research aim to analyze the determinants of cash holdings and the excess value on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period.Model research analysis using Structural Equation Modeling (SEM). The independent variables are firm size, leverage, cash flow, net working capital and growth equity. And the dependent variable is the excess cash holdings and value. This study uses panel data from 320 observational data of companies that have been listed in the Indonesia Stock Exchange in the period 2011-2015. The results showed that 1) cash flow, net working capital have significant effect on cash holdings. 2) leverage, firm size, growth equity doesn’t have significant effect on cash holdings. 3) cash holdings have significant effect on the excess value. 4) cash flow, net working capital, leverage doesn’t have significant effect on the excess value. 5) firm size, growth equity doesn’t have significant effect on the excess value.This research aim to analyze the determinants of cash holdings and the excess value on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period.Model research analysis using Structural Equation Modeling (SEM). The independent variables are firm size, leverage, cash flow, net working capital and growth equity. And the dependent variable is the excess cash holdings and value. This study uses panel data from 320 observational data of companies that have been listed in the Indonesia Stock Exchange in the period 2011-2015. The results showed that 1) cash flow, net working capital have significant effect on cash holdings. 2) leverage, firm size, growth equity doesn’t have significant effect on cash holdings. 3) cash holdings have significant effect on the excess value. 4) cash flow, net working capital, leverage doesn’t have significant effect on the excess value. 5) firm size, growth equity doesn’t have significant effect on the excess value.This research aim to analyze the determinants of cash holdings and the excess value on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period.Model research analysis using Structural Equation Modeling (SEM). The independent variables are firm size, leverage, cash flow, net working capital and growth equity. And the dependent variable is the excess cash holdings and value. This study uses panel data from 320 observational data of companies that have been listed in the Indonesia Stock Exchange in the period 2011-2015. The results showed that 1) cash flow, net working capital have significant effect on cash holdings. 2) leverage, firm size, growth equity doesn’t have significant effect on cash holdings. 3) cash holdings have significant effect on the excess value. 4) cash flow, net working capital, leverage doesn’t have significant effect on the excess value. 5) firm size, growth equity doesn’t have significant effect on the excess value.This research aim to analyze the determinants of cash holdings and the excess value on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period.Model research analysis using Structural Equation Modeling (SEM). The independent variables are firm size, leverage, cash flow, net working capital and growth equity. And the dependent variable is the excess cash holdings and value. This study uses panel data from 320 observational data of companies that have been listed in the Indonesia Stock Exchange in the period 2011-2015. The results showed that 1) cash flow, net working capital have significant effect on cash holdings. 2) leverage, firm size, growth equity doesn’t have significant effect on cash holdings. 3) cash holdings have significant effect on the excess value. 4) cash flow, net working capital, leverage doesn’t have significant effect on the excess value. 5) firm size, growth equity doesn’t have significant effect on the excess value.